Determination of Antagonistic Effects of Sludge and Urine-Associated Bacteria against Staphylococcus aureus and Escherichia coli - Kenneth, Imarenezor Edobor Peter; Ngozi, Opara Christiana; Samson, Efere Yarwadum (Darul Yasin Al Sys, 2026)
Abattoirs, due to their very many activities, is a source of microbial diversity, many of which are able to prevent the growth of other closely related bacteria. Hence, this work was carried out to isolate and identify bacteria from sludge and urine, and evaluate their antagonistic effects against Staphylococcus aureus and Escherichia coli. The antagonistic effects of bacterial pathogens from abattoir sludge against Staphylococcus aureus and Escherichia coli. The culture and identification of bacteria from abattoir sludge was done using standard microbiological techniques and the bacterial antagonism assay was done using the overlay method. From the abattoir sludge, Bacillus species (37.5%) was the most prevalent, followed by Shigella species (12.5%), Escherichia coli (12.5%), Staphylococcus aureus (12.5%), Proteus species (12.5%), and Klebsieilla. species (12.5%). The bacterial isolates were most resistant to Ciprofloxacin, Cefotaxime, Cefuroxime, Imipenem and most sensitive to Nitrofurantoin, Nalixidic Acid, Gentamicin, Erythromycin, Ofloxacin, AZN. From the study, none of these abattoir sludge-associated bacteria showed antagonistic effect against Staphylococcus aureus and against Escherichia coli. This study demonstrates the antagonistic potential of sludge and urine-associated bacteria against Staphylococcus aureus and Escherichia coli. The identified isolates, particularly Pseudomonas aeruginosa and Bacillus subtilis, exhibited significant inhibitory activity, suggesting their potential as sources of novel antimicrobial compounds. These findings highlight the importance of exploring environmental and human-associated microbiota for bioactive molecules that could address the growing challenge of antibiotic resistance.